Integrating Collaboration and Communication Skills: Development of Discovery Learning-Based Science Module - Prahastiwi, Rima Buana; Sholehah, Najah (Universitas Islam Negeri (UIN) Mataram, 2024)
This research is a development study with the final outcome being a discovery learning-based science module as an alternative to integrate collaboration and communication learning skills. The development of the integrated science module aims to create innovative teaching materials that can be applied as an alternative for learning and support independent or student-centered learning. The integrated science module is developed based on discovery learning. The goal of discovery learning is to provide students with practice in various skills, particularly collaboration and communication skills. The development research method used is the ADDIE design development method. This method was chosen because it is a fundamental development method that is easy to apply. The stages of the ADDIE design development process include Analyze, Design, Development, Implementation, and Evaluation. The product feasibility test involved 30 students from MTs Miftahul Ma’arif Pelambik, with assessments conducted by media and content experts. The media feasibility test resulted in a score of 92.7%, categorized as very feasible. The content feasibility test resulted in a score of 96.4%, also categorized as very feasible. The student response score to the development of the integrated science module ranged from 3.7 to 3.9 out of a maximum score of 4. The results of this study imply that the module is valid and feasible for use in teaching, particularly as an alternative for collaboration and communication learning skills.